Community knowledge and attitudes toward bird conservation in Bagek Kembar, West Lombok, Indonesia - MUHAMMAD SYAZALI; GITO HADIPRAYITNO; MOHAMMAD LIWA ILHAMDI; I WAYAN SUANA; GDE CAHYADI WIRAJAGAT; SAFARIYANTI MANISA; SRI APRILIA NUR LARASATI (Society for Indonesian Biodiversity, 2026)
Abstract. Syazali M, Hadiprayitno G, Ilhamdi ML, Suana IW, Wirajagat GC, Manisa S, Larasati SAN. 2026. Community knowledge and attitudes toward bird conservation in Bagek Kembar, West Lombok, Indonesia. Biodiversitas 27 (2): d270202. https://doi.org/10.13057/biodiv/d270202. Birds in Bagek Kembar, West Lombok, Indonesia, play an important ecological role and support emerging birdwatching ecotourism. However, habitat changes and human activities continue to threaten their sustainability. This study aims to (i) assess community knowledge, perceptions, and attitudes toward bird conservation, (ii) examine the influence of family and teacher roles, and (iii) analyze the structural relationships among knowledge, perception, and attitude using the knowledge attitude behavior framework. Data were collected from 140 respondents selected by stratified random sampling across four education levels using a 20 item Likert-scale questionnaire. Data were analyzed using ANOVA, Chi-square tests, Pearson correlation, and structural equation modeling. The results showed that community knowledge (2.29 ± 0.40), perceptions (2.04 ± 0.73), and attitudes (2.96 ± 0.55) were generally in the moderate category, with significant differences among education levels (p < 0.01). Teachers exerted stronger influence (67.29%) than families (51.47%), especially at higher education levels. Knowledge directly influenced attitudes (β = 0.41, p < 0.001) and indirectly through perception (β = 0.36, p < 0.01), with a good model fit (CFI = 0.93; RMSEA = 0.05). These findings demonstrate that improving ecological knowledge alone is insufficient without strengthening positive perceptions. Integrating conservation education into local schools and community based ecotourism is essential for sustaining bird conservation in Lombok.